Evaluating Rhodopseudomonas palustris, Saccharomyces cerevisiae, and Bacillus licheniformis as substitutes for microalgae food source: Impacts on growth, survival, gut microbiota, and nutrition of Cyclina sinensis - Shiyu Yan; Shizhao Du; Wanyi Song; Guolong Zhou; Chaohua Wang; Hanfeng Zheng; Zhengyi Li; Huan Yang; Yihua Chen; Zhiguo Dong (Aquaculture Reports)
The cultivation of microalgae is constrained by factors such as temperature and light intensity, which imposes huge economic burdens and risks on shellfish farming. Food source microorganisms have been extensively utilized across various aquaculture sectors as alternatives to microalgae food source, demonstrating positive effects. This study investigated the effect of Bacillus licheniformis, Saccharomyces cerevisiae, and Rhodopseudomonas palustris on the growth, survival, metamorphosis, intestinal flora, and nutritional indicators of life stages of Cyclina sinensis. Replacement of microalgae with R. palustris and B. licheniformis resulted in increased larval growth, survival, and metamorphosis rates. R. palustris had positive effects as a food source for D-shaped larvae during their transition to the creeping larval stage, whereas R. palustris and S. cerevisiae resulted in excellent growth performance of juvenile C. sinensis. All three microorganisms enhanced the intestinal microbiome composition of C. sinensis, leading to an increase in beneficial microorganisms that then formed the predominant microbial community. R. palustris also optimized the intestinal colony structure, whereas B. licheniformis adversely affected the spats by stimulating the intestinal flora. S. cerevisiae positively impacted amino acid synthesis and accumulation, particularly those contributing to the umami flavor. R. palustris enhanced the efficiency of nutrient absorption and transformation, while also conferring a benefit on fat accumulation. In summary, these results highlight the feasibility of using R. palustris as a microalgal food source substitute, showing positive effects on the overall performance of C. sinensis. B. licheniformis shows some potential as a initial larval feed, whereas S. cerevisiae could be used as feed for juveniles and adults.